The carbohydrate-binding promiscuity of Euonymus europaeus lectin is predicted to involve a single binding site. (10th September 2014) - Agostino, Mark; Velkov, Tony; Dingjan, Tamir; Williams, Spencer J; Yuriev, Elizabeth; Ramsland, Paul A
Abstract : Euonymus europaeus lectin (EEL) is a carbohydrate-binding protein derived from the fruit of the European spindle tree. EEL was first identified for its erythrocyte agglutinating properties and specificity for B and H blood groups. However, a detailed molecular picture of the structural basis of carbohydrate recognition by EEL remains to be developed. In this study, we performed fluorescence titrations of a range of carbohydrates against EEL. Binding of EEL to a wide range of carbohydrates was observed, including a series of blood group-related carbohydrates, mannosides, chitotriose and sialic acid. Affinity was strongest for carbohydrates with H-related structures and the B trisaccharide. A homology model of EEL was produced from templates identified using the HHPred server, which employs hidden Markov models (HMMs) to identify templates. The HMM approach identified that the best templates for EEL were proteins featuring a ricin B-like (R-type) fold. Separate templates were used to model the core and binding site regions of the lectin. Through the use of constrained docking and spatial comparison with a template ligand, binding modes for the carbohydrate ligands were predicted. A relationship between the experimental binding energies and the computed binding energies of the selected docked poses was determined and optimized. Collectively, our results suggest that EEL utilizes a single site for recognition of carbohydrates terminating in a variety of monosaccharides.